PENGARUH KOMPETENSI, KOMPLEKSITAS TUGAS DAN SKEPTISME PROFESIONAL TERHADAP KUALITAS AUDIT - Anugerah, Rita; Akbar, Sony Harsono (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This research aims to determine the effect of competence, task complexity andprofessional skepticism of auditors on audit quality as Riau Province Inspectorate.By using multiple regression analysis, 129 auditors working in the Inspectoratesprovincial government, municipal government inspectorate 2 and 10 districtinspectorate were respondents of this study. The results showed that thecompetence and professional skepticism significant effect on audit quality, while thecomplexity of the task has no effect on audit quality. The implications of this studyemphasize the importance of the knowledge audit and the auditors professionalskepticism applied to every assignment auditors.Keywords: Competence, task complexity, and quality audit professional skepticism